Consuming energy drinks at the age of 14 predicted legal and illegal substance use at 16. (2nd September 2016) - Barrense‐Dias, Yara; Berchtold, André; Akre, Christina; Surís, Joan‐Carles
Abstract: Aim: This study examined whether consuming energy drinks at the age of 14 predicted substance use at 16. Methods: We followed 621 youths from an area of Switzerland who completed a longitudinal online survey in both 2012 and 2014 when they were 14 and 16 years of age. At 14, participants, who were divided into nonenergy drink users (n = 262), occasional users (n = 183) and regular users (n = 176), reported demographic, health‐related and substance use data. Substance use at 16 was assessed through logistic regression using nonusers as the reference group and controlling for significant variables at 14. Results: At the bivariate level, energy drink consumption was associated with substance use at both 14 and 16. Energy drink consumers were also more likely to be male, older, less academic, sleep less on schooldays and live in an urban area. In the multivariate analysis, smokers, alcohol misusers and cannabis users at the age of 16 were significantly more likely to have been regular energy drink users at the age of 14. Conclusion: Consuming energy drinks at 14 years of age predicted using legal and illegal substances at 16. Health providers should screen young adolescents for energy drink use and closely monitor weekly users. Abstract :